Species diversity of myrmecofauna and araneofauna associated with agroecosystem and forest fragments and their interaction with carabidae and staphylinidae (Coleoptera) - Haddad, Gianni Queiroz [UNESP]; Cividanes, Francisco Jorge [UNESP]; Martins, Ivan Carlos Fernandes [UNESP] (De Gruyter, 2011)
Faunistic and statistical analyses of species diversity of the mimercofauna and araneofauna associated with variously managed agricultural fields and adjacent forest fragments and their interactions with Carabidae and Staphylinidae (Coleoptera) are needed to identify the key species affecting the dynamics within the arthropod population affecting the agroecosystem. This knowledge is needed to devise more effective integrated pest management programs. In this study, a population survey of ants (Hymenoptera: Formicidae) and spiders (Araneae) was performed. The aims of this work were to determine the dominant species, to examine the fauna through several indexes and to evaluate the occurrence of adverse interaction between these arthropods and Carabidae and Staphylinidae (Coleoptera). The experimental areas were located in Guara City, So Paulo, Brazil, which consists of forest fragments and soybean/corn crops under no-tillage and conventional systems. The arthropods were sampled by pitfall traps from Nov 2004 to Apr 2007. The traps were distributed along 2 transects of 200 m long with 100 m each in 2 fields in corn/soybean rotations and 100 m in the forest fragments adjacent to these agricultural fields. The fauna were characterized by diversity indices, evenness, similarity, abundance, dominance, frequency and consistency and interspecific interactions by Pearson's correlation. The ants, Pheidole spp. and Camponotus blandus, and the spider, Trochosa sp. were dominant in the no-till and conventionally tilled corn/soybean fields. The diversities of spider and ant species were high in the forest fragments, and at the forest-crop interface. Indeed ant species were highly and similarly diverse in all of the habitats, whereas the diversity of ant species was substantially less in no-till than in conventionally tilled corn/soybean fields. The density of the ant, Pheidole sp.1, correlated negatively with that of spiders, carabids, and staphylinids in the no-till soybean/corn fields. Copyright © 2011 BioOne All rights reserved.
Keywords: biological control; diversity; faunistic analysis; interaction; predators